2005
DOI: 10.1111/j.1460-9592.2005.01650.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of caudal ketamine with lidocaine or tramadol administration for postoperative analgesia of hypospadias surgery in children

Abstract: Caudal ketamine (0.25 mg.kg(-1)), plus lidocaine (2% 2 mg.kg(-1)) significantly reduced sevoflurane concentration compared with ketamine (0.25 mg.kg(-1)) + tramadol (1 mg.kg(-1)). We suggested that both ketamine + lidocaine and ketamine + tramadol provided very effective and long duration of analgesia, similarly. However, analgesia quality is superior in the ketamine-lidocaine group postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…In our study, the duration and extent of sensory block provided by spinal bupivacaine were adequate in both groups. The mean operation time was 50 min in our series, a time period comparable to that of hypospadias surgeries reported by others (15,16). We considered complete motor block in the legs as the starting point of anesthesia.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, the duration and extent of sensory block provided by spinal bupivacaine were adequate in both groups. The mean operation time was 50 min in our series, a time period comparable to that of hypospadias surgeries reported by others (15,16). We considered complete motor block in the legs as the starting point of anesthesia.…”
Section: Discussionsupporting
confidence: 85%
“…It has been reported that epidural co-administration of ketamine and lidocaine provided very effective and long duration of post-operative analgesia in children (Gunduz et al 2006). Co-administration of ketamine and lidocaine epidurally increased duration of caudal analgesia in cats and dogs compared with administration of lidocaine or ketamine alone (DeRossi et al 2009;DeRossi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The contributory effect of the addition of ketamine, an N-methyl-D-aspartate (NMDA) antagonist, was evaluated when the drug is delivered via caudal [6, 8], epidural [18, 19], and spinal [20, 21] routes. In all these studies, addition of ketamine with antagonism to NMDA receptors and an axonal conduction block may also contribute to the analgesic mechanism of regional ketamine to different local anesthetics which provided a success on both block duration and quality.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been published on the effects of different adjuvants on local anesthetics for axillary brachial plexus block [15]. Tramadol and ketamine are the most common adjuvants used with local anesthetics [6, 7]. …”
Section: Introductionmentioning
confidence: 99%